The expression of discontent in Chile: culture, public sphere, and social struggles - Del Valle Orellana, Nicolás (Revista de Humanidades de Valparaíso, 2021)
This article develops the concepts of the public sphere, cultural malaise and social suffering in critical theory to think of social struggles as forms of social protest and political protest that occurred since October 2019 in Chile. The article explores the thesis on social discontent, which maintains that recent social struggles are a public expression of the unrest cultivated by processes of social modernization. According to the author, beyond the normative justification in reasons and arguments regarding the conditions of injustice that affect the agents in struggle, the social critique emerges from the social suffering that finds its place in the materiality of the discourses, images and bodies in the public sphere.